2009
DOI: 10.1021/nn900173e
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry and Structure of Poly(amidoamine) Dendrimer−Lipid Complexes

Abstract: The energetics, stoichiometry, and structure of poly(amidoamine) (PAMAM) dendrimer-phospholipid interactions were measured with isothermal titration calorimetry (ITC), transmission electron microscopy (TEM), atomic force microscopy (AFM), dynamic light scattering (DLS), and molecular dynamics (MD) simulations. Dendrimers of sixth-generation and smaller interacted with the lipids at an average stoichiometry and enthalpy proportional to the number of primary amines per dendrimers (4.5 ± 0.1 lipids/primary amine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 56 publications
12
104
1
2
Order By: Relevance
“…22 Superparamagnetic iron oxide (SPIO) and gold (Au) nanoparticles have been reported in the field of tumor disgnostics and cancer treatment. [9][10][16][17][18][19][20][21] Semiconducting nanocrystals, e.g. quantum dots, were used to improve biological imaging for medical diagnostics, 14 and these crystals were able to offer resolutions up to 1,000 times better than conventional dyes used in many biological tests.…”
Section: Nanoparticle -Membrane Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Superparamagnetic iron oxide (SPIO) and gold (Au) nanoparticles have been reported in the field of tumor disgnostics and cancer treatment. [9][10][16][17][18][19][20][21] Semiconducting nanocrystals, e.g. quantum dots, were used to improve biological imaging for medical diagnostics, 14 and these crystals were able to offer resolutions up to 1,000 times better than conventional dyes used in many biological tests.…”
Section: Nanoparticle -Membrane Interactionmentioning
confidence: 99%
“…[19][20][21][22] Inductively coupled plasma optical emission spectrometry (ICP-OES) or mass spectrometry (MS) has also been used, for example, to probe the interaction between functionalized Au nanoparticles and silica sphere-supported lipid membranes (SSLMs) by measuring the concentrations of Au nanoparticles both in the aqueous electrolytes (supernatant) and in/on the lipid bilayers. 23 The electrophysiological approach 24 coupled with the droplet-in-oil methodology has been employed to study the interaction between nanoparticles and cell membranes.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…It seems that besides the weakly correlated, fragmented lamellae, small proportion of micelles or other highly curved vesicles are present. Since G5 PAMAM dendrimers do not have a radius high enough to support individually a surrounding vesicle [17], aggregated dendrimers should be in the core of these assemblies. The microscale inhomogeneities observed on the TEM pictures give an explanation for the complex main transition peak on the DSC curve (Fig.2.).…”
Section: Changes In Thermal Behaviormentioning
confidence: 99%
“…The interaction between cell membranes and nanocarriers, such as dendrimers, is very important, because in the most cases carriers have to get across the lipid bilayer without disrupting it. Previous studies based on atomic force microscopy (AFM) [12][13][14][15][16][17] isothermal titration calorimetry (ITC), fluorescence correlated spectroscopy (FCS) [17][18], in vitro experiments [13,[19][20] and molecular dynamics simulations (MD) [14,17,[21][22][23][24] showed that cationic dendrimers disrupt lipid bilayers by forming holes on the bilayer surface and may remove lipids from it. The degree of the disruption depends on the size and charge of the dendrimer.…”
Section: Introductionmentioning
confidence: 99%
“…The binding strength between dendrimer-guest complexes has been determined by isothermal titration calorimetry(ITC) [26][27][28][29], high performance liquid chromatography (HPLC) [30] and fluorescence spectroscopy [31][32][33]. Detailed conformations of dendrimers interacting with guest molecules have been studied by nuclear magnetic resonance(NMR) [34][35][36] and the size of the dendrimer-guest complexes has been measured by dynamic light scattering (DLS) [22,31].…”
Section: Introductionmentioning
confidence: 99%